2015
DOI: 10.1097/md.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Ashkenazi Jewish Origin Protects Against Formation of Antibodies to Infliximab and Therapy Failure

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Immunogenicity is a multifactorial phenomenon, influenced by patient (genetic background, ethnicity), disease (type, activity), treatment (episodic vs. scheduled, co‐administration of immunosuppressive agents) and/or drug‐related factors (dosing, route of administration, product aggregation and denaturation), that can have a significant impact both on the efficacy and safety of biological therapies …”
Section: Resultsmentioning
confidence: 99%
“…Immunogenicity is a multifactorial phenomenon, influenced by patient (genetic background, ethnicity), disease (type, activity), treatment (episodic vs. scheduled, co‐administration of immunosuppressive agents) and/or drug‐related factors (dosing, route of administration, product aggregation and denaturation), that can have a significant impact both on the efficacy and safety of biological therapies …”
Section: Resultsmentioning
confidence: 99%
“…Patients receiving MTX were significantly less likely to develop ADAs and 83% of ADA-positive patients developed loss of response compared with 6% of ADA-negative patients. Genetic susceptibility to risk of ADA formation has been suggested in recent studies that found that an Ashkenazi Jewish ancestry was protective of ADA formation, with a relative risk reduction on par with concomitant DMARD therapy [48]. Together these studies highlight the potential importance of therapeutic drug level and ADA monitoring in patients receiving anti-TNF-α therapy and is evidenced by their routine monitoring in many patient care settings.…”
Section: Immunogenicity and Therapeutic Drug Monitoring With Biologicmentioning
confidence: 91%
“…Smoking has often been associated with significantly lower rates of response to anti-TNF for CD [Arnott et al 2003; Cohen et al 2012; Juillerat et al 2015; Ungar et al 2015a]. Other reports did not observe this association [Fefferman et al 2004; Orlando et al 2005].…”
Section: Response To Previous Therapies Disease Phenotype and Locationmentioning
confidence: 99%
“…In an Israeli study, Ashkenazi Jewish origin was associated with a less frequent formation of anti-TNF antibody formation compared with the prevalence in Jews of Sephardic origin, in both UC and CD. However, genetic analysis was not performed [Ungar et al 2015a].…”
Section: Antidrug Antibodiesmentioning
confidence: 99%